Analisis Nilai Karakter dalam Dongeng Pada Buku Siswa Tema 8 Daerah Tempat Tinggalku Kelas IV Sekolah Dasar - Satriyo Agung Budi Harjono; Ikha Listyarini; Mei Asri Untari (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The value of character in learning is a must. This study analyzes the value of characters in students' books. This study uses a qualitative approach, the data analysis technique is qualitative descriptive of a literary work by looking for the character values contained therein. The data in this study were obtained through observation, interviews, documentation, listening and notes. The results of the study showed that the book "Student Book Theme 8 Where I Live in Class IV Elementary School" contained 34 character values with reference to 18 character values of the Ministry of National Education, the character values were religious 2.94%, honest 11.76%, tolerance and discipline did not exist. , hard work 17.64%, creativity appears 8.82%, Independent 2.94%, Democratic 8.82%, Curiosity 2.94%, National Spirit 2.94%, Love the homeland and appreciate achievement none . Friendly/Communicative 8.82%, Peaceful Love 2.94%, No Likes to Read, Environmental Care 5.88%, Social Care 11.76% and Responsibility 11.76%. This book can be used as a medium in character education for elementary school children. Good character so that it can be applied in the values of life.